Variants in RBP4 and AR genes modulate age at onset in familial amyloid polyneuropathy (FAP ATTRV30M) - Santos, D (2016)
Familial amyloid polyneuropathy (FAP) ATTRV30M is a neurodegenerative disorder due to point mutations in the transthyretin gene, with V30M being the commonest. FAP ATTRV30M shows a wide variation in age at onset (AO) between clusters, families and generations. Portuguese patients also show remarkable AO differences between genders. Genes found to be associated with FAP ATTRV30M pathways may act as AO modifiers. Our aim was to further explore the role of APCS and RBP4 genes and to study for the first time the involvement of sex-linked genetic modifiers - AR and HSD17B1 genes - in AO variation in Portuguese families. We collected DNA from a sample of 318 patients, currently under follow-up. A total of 18 tagging SNPs from APCS, RBP4, AR and HSD17B1 and 5 additional SNPs from APCS and RBP4 previously studied were genotyped. To account for nonindependency of AO between members of the same family, we used generalized estimating equations (GEEs). We found that APCS and RBP4 were associated with late AO. In addition, rs11187545 of the RBP4 was associated with an early AO. For the AR, in the male group three SNPs were associated with an early AO, whereas in the female group four were associated with both an early and later AO. These results strengthened the role of APCS and RBP4 genes and revealed for the first time the contribution of AR genes as an AO modifier in both males and females. These findings may have important implications in genetic counseling and for new therapeutic strategies.